Intensification of Near‐Surface Currents and Shear in the Eastern Arctic Ocean. Issue 16 (14th August 2020) - Polyakov, Igor V.; Rippeth, Tom P.; Fer, Ilker; Baumann, Till M.; Carmack, Eddy C.; Ivanov, Vladimir V.; Janout, Markus; Padman, Laurie; Pnyushkov, Andrey V.; Rember, Robert
Abstract: A 15‐year (2004–2018) record of mooring observations from the upper 50 m of the ocean in the eastern Eurasian Basin reveals increased current speeds and vertical shear, associated with an increasing coupling between wind, ice, and the upper ocean over 2004–2018, particularly in summer. Substantial increases in current speeds and shears in the upper 50 m are dominated by a two times amplification of currents in the semidiurnal band, which includes tides and wind‐forced near‐inertial oscillations. For the first time the strengthened upper ocean currents and shear are observed to coincide with weakening stratification. This coupling links the Atlantic Water heat to the sea ice, a consequence of which would be reducing regional sea ice volume. These results point to a new positive feedback mechanism in which reduced sea ice extent facilitates more energetic inertial oscillations and associated upper‐ocean shear, thus leading to enhanced ventilation of the Atlantic Water. Plain Language Summary: Previous studies demonstrated that in recent years density gradients above the warm and salty intermediate (~150–900 m) water of Atlantic origin in the eastern Arctic Ocean have weakened, allowing stronger upward transport of heat to the bottom of the sea ice. Using mooring observations, we show that this weakening of stratification has been accompanied by stronger upper‐ocean currents and their vertical shear and by increasing coupling between the wind and sea ice with upper ocean currents and shear. Most of this enhanced energy and shear is in the semidiurnal band, which includes baroclinic tides and wind‐driven inertial oscillations. The increased shear together with the weakening stratification indicate a greater potential for shear‐driven turbulent mixing. We propose a new process, the ice/ocean‐heat positive feedback, that can accelerate current sea ice loss and impede the rate of recovery of eastern Arctic sea ice even if large‐scale climate warming conditions relax. Key Points: Currents and associated shear in the upper 50 m in the eastern Eurasian Basin increased in the 2010s Increased currents and shear are dominated by accelerating currents in the semidiurnal (inertial and tidal) band There was an increasing coupling between wind, ice, and oceanic currents in the eastern Eurasian Basin over 2004–2018